Sexual Orientation and the Canadian Labour Movement - Hunt, Gerald (Relations industrielles / Industrial Relations, 1997)
The response of the Canadian labour movement to sexual orientation discrimination has been mixed and uneven. The Canadian Labour Congress, along with several provincial federations and a grouping number of unions, have taken a leadership role in promoting equal rights for gays and lesbians, while other labour organizations have done nothing at all. Public sector and Canadian based unions are much more likely to have been active than have American-based unions, even though there are important exceptions to these trends. These developments are partially explained by regional dynamics, membership demographics, degree of activism, the presence of women's committees, and organizational leadership.